2016
DOI: 10.1002/acr.22914
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Dementia in Patients With Systemic Lupus Erythematosus: A Nationwide Population‐Based Cohort Study

Abstract: Patients with SLE have a higher risk of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In fact, some of these conditions can, in their selves, induce a cognitive impairment. An example of this is SLE [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some of these conditions can, in their selves, induce a cognitive impairment. An example of this is SLE [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…A cohort and cross‐sectional study demonstrated RA patients are at higher risk of developing dementia but there is high statistical heterogeneity and no causality in it . A population‐based cohort study found that the risk of developing dementia in patients with systemic lupus erythematosus (SLE) is two times higher than patients without SLE . Studies showed that SLE may lead to the destruction of central nervous system and vascular lesions due to antiphospholipid antibodies and drug use, which leads to dementia …”
Section: Introductionmentioning
confidence: 99%
“…5 A population-based cohort study found that the risk of developing dementia in patients with systemic lupus erythematosus (SLE) is two times higher than patients without SLE. 8 Studies showed that SLE may lead to the destruction of central nervous system and vascular lesions due to antiphospholipid antibodies and drug use, which leads to dementia. [9][10][11][12] However, there is no large epidemiologic study to demonstrate the relationship between dementia and rheumatic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These include MS, [104][105][106] sarcoidosis, [107][108][109] primary angiitis of the CNS, [110][111][112] amyloid β-related angiitis, 113 Susac's syndrome, 114,115 Rasmussen's encephalitis and other inflammatory epilepsies, 116,117 and systemic rheumatologic conditions. [118][119][120][121][122][123][124] Diagnosing Autoimmune Dementia…”
Section: Aid-ae In Patients With Other (Atypical) Causes Of Aementioning
confidence: 99%